Crianças com e sem deficiência auditiva: O equilíbrio na fase escolar - Rodrigues, Ariele Troiano; Bertin, Vanessa; Vitor, Leonardo George; Fujisawa, Dirce Shizuko [UNESP] (FapUNIFESP (SciELO), 2014)
The ability to maintain one's balance is a prerequisite for carrying out several daily living activities. To adjust one's balance, the postural control system requires information about the relative positions of the body segments and the magnitude of the acting forces. The information comes from several systems: visual, vestibular and somatosensory. There may be concerns in the process of acquiring basic motor skills for some individuals with sensorineural hearing impairments, due to problems with balance. The aim of this study was to compare balance in children with and without hearing impairments from nine to 12 years. The sample was made up of 20 children, 10 with and 10 without hearing impairments. The Pediatric Balance Scale - PBC - (Brazilian version) and the Range Test were applied in order to assess balance. Regarding the PBC scores, children with hearing impairment had a mean score of 55, while hearing children presented with a men score of 56 points (p = 0.007). On the Range Test, children with and without hearing impairments had the following mean results: previous range - 24/29 (p=0.021); right lateral reach - 16/22 (p=0.001); left lateral reach - 14.5/22 (p=0.002), respectively. The results suggest that children with sensorineural hearing impairments had balance deficits, compared to hearing children. This fact may be related to sensorineural hearing impairment, since children with hearing impairments can also present alterations in balance caused by deficit in quantity and/or quality of information coming from the vestibular apparatus. Thus, it was possible to identify that children with hearing impairments present alterations in balance, when compared to hearing children.
Children with and without hearing impairment: Balance during school years
Keywords: Assessment of abilities; Child; Hearing impairment; Special education